US Foreign Policy on Transitional Justice and Democratization in Tunisia: Pacted Transition or Democracy Reduction? - Oussema Othmeni (European Journal of American Studies)
The United States of America (US) committed nearly $1.4 billion in foreign assistance to Tunisia in support of its democratic transition and transitional justice process between 2011 and 2020. This paper seeks to identify and assess the ideational frameworks guiding the distribution of US assistance, and influencing US foreign policy behavior, throughout the democratization and transitional justice period in Tunisia. It provides considerable evidence showcasing the existence of two prevalent schools of thought in US policymaking circles: The first school believes that the US invested in the notion of Pacted Transitions, which advocates for rapid transitions through political compromise and power-sharing mechanisms without necessarily promoting grassroots democratic reform. This can indirectly explain the US emphasis on security sector assistance and the relative marginalization of transitional justice objectives mainly in terms of institutional vetting, lustration, and reform. The second school puts forward a Democracy Reduction Critique, arguing instead that US policymakers fell for the electoral democracy fallacy and fetishized the role of civil society. This paper critically accounts for both schools and argues that they represent two sides of the same coin.